2018
DOI: 10.1016/j.nicl.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to task positive and task negative networks during executive functioning in Mild Cognitive Impairment

Abstract: Poor executive functioning increases risk of decline in Mild Cognitive Impairment (MCI). Executive functioning can be conceptualized within the framework of working memory. While some components are responsible for maintaining representations in working memory, the central executive is involved in the manipulation of information and creation of new representations. We aimed to examine the neural correlates of these components of working memory using a maintenance working memory and visuospatial reasoning task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 51 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…The superior and middle frontal gyri are involved in a series of cognitive processes, such as executive function and working memory (Kim et al, 2014;Zamora et al, 2016), while the lateral temporal cortex is more involved in episodic memory (Luo et al, 2018). These cognitive functions are typically impaired in AD and MCI patients (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018). Studies have suggested an involvement of the lateral frontal and temporal cortical regions in aMCI (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The superior and middle frontal gyri are involved in a series of cognitive processes, such as executive function and working memory (Kim et al, 2014;Zamora et al, 2016), while the lateral temporal cortex is more involved in episodic memory (Luo et al, 2018). These cognitive functions are typically impaired in AD and MCI patients (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018). Studies have suggested an involvement of the lateral frontal and temporal cortical regions in aMCI (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These cognitive functions are typically impaired in AD and MCI patients (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018). Studies have suggested an involvement of the lateral frontal and temporal cortical regions in aMCI (Bell-McGinty et al, 2005;Clément and Belleville, 2010;Teipel et al, 2010;Liang et al, 2011;Scheller et al, 2014;Verfaillie et al, 2016;Melrose et al, 2018). For instance, a study (Verfaillie et al, 2016) combining the R-fMRI and CSF showed that the regional homogeneity values were associated with the Aβ level of the superior temporal gyrus in patients with sd-aMCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, dependent on individual network excitability, network-level response to stimulation might vary in MCI patients and HE. Suboptimal network activation in MCI patients [93,94] might benefit from activation with atDCS if applied in parallel to training. In line with this hypothesis, initially low-performing HE, that likely also show suboptimal network functioning [95,96], showed greater benefit from atDCS application compared to initially high-performing HE.…”
Section: Effects Of Atdcs On Training Successmentioning
confidence: 99%